Myoepithelial Cell-Rich Pleormorphic Adenoma of Minor Salivary Gland of Parapharyngeal Space - Digvijay Singh Rawat; Divij Sonkhya; Nishi Sonkhya; Shubha Gupta (Case Reports in Otolaryngology)
Parapharyngeal space tumors are rare and constitute only 0.5–1.0% of head and neck tumors. Minor salivary gland tumor is still rare in parapharyngeal space. We are reporting a case of pleomorphic adenoma of minor salivary gland of parapharyngeal space. A 42-year-old female presented with a history of mass in the oropharynx for 3 years. She presented with “hot potato voice” and dysphagia. CECT and MRI were done, showing large parapharyngeal space tumor. FNAC was suspicious for tumor of nerve cell origin. Tumor was excised using “paramedian mandibulotomy with mandibular swing approach”. Histopathological examination was inconclusive, suggesting possibility of extraskeletal myxoid chondrosarcoma, solitary fibrous tumor, neurogenic tumor. On immunohistochemistry, tumor was positive for cytokeratin, EMA (dim), S-100, and P 63 and negative for SMA thus proving the case as myoepithelial cell-rich pleomorphic adenoma.